FEATURES OF THE FORMATION OF PROFESSIONALLY IMPORTANT FEATURES OF ATTENTION IN PHYSICAL EDUCATION OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS (KONFERENSIYA, 2026)
This article raises the issue of the importance of the targeted formation of the characteristics of mental processes that ensure the effectiveness of performing professional tasks in future specialists. Based on a comparative analysis of the content of the training process of highly qualified athletes and the physical education of students, the need to implement special exercises that contribute to the targeted formation of professionally important features of attention is substantiated.